CEMENT MATERIAL DEVELOPMENT USED FOR CEMENTING UNDERGROUND COAL GASIFICATION WELL - Miftahul Huda (Puslitbang tekMIRA, 2018)
R&D Centre for Mineral and Coal Technology, the Ministry of Energy and Mineral Resources developes an underground coal gasification (UCG) technology including its UCG test in a coal mine at Musi Banyuasin regency, South Sumatra. The UCG is safer than the underground mine since there is no worker underground however there is a concern in risk of ground water pollution. One of the mthods to reduce the risk is a proper instalation of well casing and cementing that seal aquifer from contact with UCG product gas. Development of special cement for cementing UCG well is needed due to its high process temperature (up to 1300°C). The objective of this research is to develop a cement material that can withstand high temperatures environtment. Domestically available an oil well cement (OWC) and a castables (CT) were used for the experiments. Single material of OWC is not suitable for cementing UCG well since the OWC compressive strength reduced drastically at heat treatment above 300°C due to decomposistion of portlandite and calcium silicate hydrate. On the other hand, there was a synergistic effect that resulted of higher compressive strength sample if 60% weight of OWC and 40% weight of CT was blended. The absence of portlandite and the presence of inert filler materials in the blend is believed to improve thermal and mechanical properties of the blend.